The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jsfa.5701
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers of meat tenderisation and its use for early classification of Asturian beef into fast and late tenderising meat

Abstract: Early monitoring (within 24 h after slaughter) of selected biomarkers in LD muscle allowed accurate prediction of ultimate meat toughness and could be used in the meat industry as a tool for early classification of beef into fast and late tenderising meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 72 publications
2
26
0
2
Order By: Relevance
“…However, a significantly higher content of PGM was measured in drip loss from meat of lambs fed with SeY (Table 3). Many studies have shown that sarcoplasmic proteins appeared as indicators of meat ageing and as biomarkers of some quality attributes, tenderness in particular (Di Luca et al, 2011;Sierra et al, 2012;Ouali et al, 2013;Bowker et al, 2014;Marino et al, 2014;Picard et al, 2015). These proteins include GAPDH, a, b, c -means with different superscripts in the same row differ significantly at P α ≤ 0.05.…”
Section: Effect Of Lamb Diets On Drip Loss Protein Profilementioning
confidence: 99%
“…However, a significantly higher content of PGM was measured in drip loss from meat of lambs fed with SeY (Table 3). Many studies have shown that sarcoplasmic proteins appeared as indicators of meat ageing and as biomarkers of some quality attributes, tenderness in particular (Di Luca et al, 2011;Sierra et al, 2012;Ouali et al, 2013;Bowker et al, 2014;Marino et al, 2014;Picard et al, 2015). These proteins include GAPDH, a, b, c -means with different superscripts in the same row differ significantly at P α ≤ 0.05.…”
Section: Effect Of Lamb Diets On Drip Loss Protein Profilementioning
confidence: 99%
“…In addition, some studies have focused on analysis of the links between the profile of sarcoplasmic proteins and meat quality traits (Mikołajczak and others ; Laville and others ; Marino and others ; Canto and others ; Gao and others ). As it was stated by Sierra and others (), post mortem changes as degradation or oxidation of sarcoplasmic proteins can provide useful information about process of conversion of muscle into meat and its effect on meat quality and its traits.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in genomics and proteomics offer the possibility of better understanding the process of conversion of muscle into meat and its effect on technological and sensory meat quality traits (Di Luca and others , , ; Sierra and others ; Picard and others ). The degree of proteolysis of myofibrillar protein has been often studied as a source of biomarkers of sensory quality characteristics, especially texture attributes (Hopkins and Geesink ; Kemp and others ; Ouali and others ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations